Analysis of the tensile response of a stranded conductor using a 3D finite element model. (February 2016) - Frigerio, M.; Buehlmann, P.B.; Buchheim, J.; Holdsworth, S.R.; Dinser, S.; Franck, Ch.M.; Papailiou, K.; Mazza, E.
Abstract: A 3D finite element modelling approach is proposed to investigate the axial force-elongation behaviour of a stranded conductor used for high voltage overhead lines. An all aluminium alloy conductor (AAAC), a four-layer conductor, is analysed based on the stress-strain response measured for individual wires. The aim of the model is to reproduce the complex deformation mechanisms and non-linearities associated with the helical shape of the wires, their contact interactions and the residual stress state from the manufacturing process. The latter is included in the model through a simulation of the stranding procedure. Simulations of the tensile response are compared to corresponding measurements. The results demonstrate improved predictive capabilities of the finite element model when compared to analytical formulae, and show that inelastic elongation at load levels significantly below the nominal yield strength of the constituent wires can be rationalized when residual stresses from the manufacturing process are included in the calculation. Highlights: A material model was devised for aluminium alloy conductor strands based on own tests. The new model was then applied in FE analyses of the tensile response of conductors. The influence of residual stresses generated during manufacture was investigated. The results from FEA were compared with observations from tests on conductors. Manufacturing history has a large effect on tensile response in the first load cycle.